2018
DOI: 10.1002/hed.25343
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions as predictors of psychological distress among head and neck cancer survivors: a longitudinal study

Abstract: Background Leventhal's commonsense model implies illness perceptions influence illness outcomes. This study examined illness perceptions among head and neck cancer survivors, and whether these predicted subsequent psychological distress. Methods A total of 124 survivors of head and neck cancer (87% nasopharyngeal carcinoma; NPC) completed measures of psychological distress (Hospital Anxiety and Depression Scale; HADS), illness perceptions (Brief Illness Perception Questionnaire; B‐IPQ), dispositional optimism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
(97 reference statements)
4
14
0
Order By: Relevance
“…The individual will concurrently construct or elaborate both cognitive and emotional representations of their symptoms and illness to relieve the adverse impacts resulting from the symptom or an illness ( Dempster et al, 2011 ). Some studies have revealed the association between illness perception and psychological distress among different populations ( Zhang et al, 2017 , 2018 , 2020b ). In this study, we first investigated the association between illness perception and psychological distress among patients with lung cancer and determined that illness perception was positively related to psychological distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual will concurrently construct or elaborate both cognitive and emotional representations of their symptoms and illness to relieve the adverse impacts resulting from the symptom or an illness ( Dempster et al, 2011 ). Some studies have revealed the association between illness perception and psychological distress among different populations ( Zhang et al, 2017 , 2018 , 2020b ). In this study, we first investigated the association between illness perception and psychological distress among patients with lung cancer and determined that illness perception was positively related to psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective, longitudinal, and observational study, illness perceptions were demonstrated as a potential predictor of psychological distress in patients with non-muscle-invasive bladder cancer ( Zhang et al, 2020b ). Meanwhile, illness perception has been found to predict psychological distress in head and neck cancer survivors ( Zhang et al, 2018 ), esophageal cancer survivors ( Dempster et al, 2011 ), and breast cancer survivors ( Zhang et al, 2017 ). However, it is not yet known whether the same association holds for patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, higher scores on the following illness perception subscales (experiencing more consequences of illness, a stronger sense of continued duration of illness, experiencing more symptoms of the illness, being more concerned about the illness, and being more emotionally affected by the illness) were associated with more psychological distress in all age groups, which is in line with other studies. [38][39][40] This information can be used to inform therapeutic approaches to working with cancer-related distress. Higher scores on two illness perception subscales (i.e., thinking your treatment can help your illness more and understanding your illness better) were associated with younger age, while higher scores on a third one (a stronger sense of continued duration of illness) was associated with higher age.…”
Section: Distress and Illness Perceptions In Thyroid Cancer 379mentioning
confidence: 99%
“…Additionally, the global QOL differed significantly between the two groups in illness perception for the identity item, and a higher global QOL was observed over the 3-month follow-up period in the strong perception group. A previous study on head and neck cancer survivors described that the illness identity captured patients' perceptions of symptom load (27). In the present study, the patients in the strong identity perception group may have exhibited a higher global QOL over the 3-month period as the patients captured their perceptions of symptom load prior to treatment.…”
Section: Discussionmentioning
confidence: 52%